The Influence Of Service Quality And Costing On The Satisfaction Of Students Of Sint Carolus Bengkulu High School - Pratiwi, Agata Intan Arista; Gayatri, Ida Ayu Made Ermeytha; Tambunan, Dennis Rydarto (Universitas Dehasen Bengkulu, 2025)
Sint Carolus High School is one of the private schools that plays a role in educating the nation's children, especially in Bengkulu. To attract students, Sint Carolus High School provides the best service, provides complete facilities and determines tuition fees with a cross subsidy system, according to the economic capacity of the parents of students. The purpose of this study was to determine the effect between service quality and cost setting on the satisfaction of Sint Carolus High School students in Bengkulu. The sample in the study amounted to 73 respondents, data collection using questionnaires and the analysis method used was quantitative method. The results of multiple linear regression analysis show the equation: Y = -2.959 + 0.353 X1 + 0.419 X2 + e, this illustrates the positive direction of regression, meaning that the variable quality of service (X1) and costing (X2) has a positive influence on student satisfaction (Y) at Sint Carolus High School Bengkulu. The magnitude of the coefficient of determination from the calculation results using SPSS can be known the coefficient of determination of R square of 0.677. This means that the value of service quality (X1) and the value of setting fees (X2) affect student satisfaction (Y) by 67.70% while the remaining 32.3% is influenced by other variables not examined in the study. So service quality and costing have a significant effect on student satisfaction.